Engaging Contextual Approach to Understand What Factors Contribute to Effective Health Promotion Campaigns Targeted for Rural Communities - Rohaya, Mohd Nor; Liew, Yu Mei (2013)
There has been a serious lack of research about the effectiveness of health promotion campaigns in the context of rural communities in Sarawak. This study attempts to address this limitation in the literature. The research aims to investigate what factors can influence the effectiveness of public health promotion campaigns targeted for rural communities. In this paper, we present and discuss the proposed conceptual framework and research design to undertake this research. We specifically engage the contextual approach proposed by Pettigrew to explore and identify factors that can affect the rural communities’ perception and understanding with regard to health information dissemination via health promotion campaigns.